A Study of Translation Strategies in Translating Personal Pronouns in Disney’s movie entitled Rapunzel into Thai Version - Iis Sujarwati; Sureena Sa ae; Syafryadin Syafryadin (International Journal of English Linguistics, Literature, and Education (IJELLE), 2022)
The aim of the study is to analyze translation strategies in the translation of personal pronouns used in the Disney movie Rapunzel into the Thai version. The objectives of the study are: 1) to describe the strategies used in the translation of personal pronouns in Rapunzel movie, and 2) to determine the frequency of each translation strategy used in the translation of personal pronouns in Rapunzel movie. The data of the study were gathered from English personal pronouns from the subtitle on DVD Rapunzel which was released in 2010. The result of the study showed that ten translation strategies based on Pokasamrit (2011), Nida (1964), and Vinay and Darbelnet (1958) were identified as used in the study. The strategies of translation were pronoun to pronoun/literal translation, explicitness to implicitness, kinship terms, formal language, informal language, editorial pronoun, addition, alterations/transposition, and inversion. The frequency of each translation strategy found was determined by considering the following elements: the formulation of personal pronouns and the differences between personal pronouns in English and Thai.